Holocene thecamoebians in freshwater Lakes on Bylot Island, northwest territories, Canada - Kliza, D.A. (D. A.); Schroder-Adams, C. (Claudia) (1999)
Thecamoebian assemblages were studied in two short cores from kettle lakes on Bylot Island, Canadian high arctic, within an area bounded by 72° and 74°N and 75° and 82°W. Cores did not provide suitable material for absolute age dating. Based on known sedimentation rates of other arctic lakes, however, the time interval covered by lake cores reflect sedimentation during the Holocene of approximately the last 5000 years. On the Bylot Island lowlands, a low species diversity with eleven thecamoebian species was identified whereas five lakes sampled on the Salmon River lowlands around Pond Inlet were barren of thecamoebians. Thecamoebian tests typically have a coarse texture. The shallower of the two lakes on Bylot Island is dominated by Difflugia globulus. The assemblage found in the deep lake contains nine taxa with a distinct transition from Difflugia globulus dominance in the lower half of the core to a Difflugia oblonga dominated assemblage in the upper half. D. oblonga prefers organic-rich substrates and its dominance coincides with an increase of organic material in the core. Late Holocene thecamoebian abundance fluctuates in the shallow lake whereas the deep lake is characterized by more constant numbers. Faunal results in both lakes show that local environmental factors have to be considered to explain paleolimnological changes.